2023
DOI: 10.14267/cjssp.2022.2.2
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Risk Preferences of High-Net-Worth Individual Investors During the Global Financial Crisis

Abstract: This paper studies how high-net-worth individual (HNWI) investors changed their risk preferences during the Global Financial Crisis (from 2007 to 2009) and how their asset allocation evolved in the same period. We had access to a confidential database from a Swiss international private bank with two samples of risk preferences questionnaires (suitability tests) filled by the same HNWI investors in 2007 and 2009. We compared the suitability tests’ suggested investment profiles to those investors’ real asset all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Individuals' educational levels are another demographic factor that appears to explain risk tolerance levels, as it is plausible to consider that individuals with more comprehensive academic backgrounds are better equipped to adopt riskier financial behaviors (e.g., Sjoberg 2000;Larkin et al 2013). Beyond sociodemographic factors, other determinants of risk tolerance have been identified, such as the national culture, in which decision-makers operate (e.g., Pyles et al 2016;Illiashenko 2019), and experiences in adverse macroeconomic conditions, especially those marked by financial crises (e.g., Malmendier and Nagel 2011;Sahm 2012;Cunha and Lobão 2022).…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals' educational levels are another demographic factor that appears to explain risk tolerance levels, as it is plausible to consider that individuals with more comprehensive academic backgrounds are better equipped to adopt riskier financial behaviors (e.g., Sjoberg 2000;Larkin et al 2013). Beyond sociodemographic factors, other determinants of risk tolerance have been identified, such as the national culture, in which decision-makers operate (e.g., Pyles et al 2016;Illiashenko 2019), and experiences in adverse macroeconomic conditions, especially those marked by financial crises (e.g., Malmendier and Nagel 2011;Sahm 2012;Cunha and Lobão 2022).…”
Section: Empirical Evidencementioning
confidence: 99%
“…Another possible limitation is that the perceived level of risk tolerance by individuals is probably not a static variable, as it may vary over time and in reaction to historically significant events. For instance, Sahm (2012) and Cunha and Lobão (2022) showed that macroeconomic conditions and the occurrence of financial crises have a significant impact on the risk tolerance levels of economic agents.…”
Section: Conclusion Limitations and Suggestions For Further Researchmentioning
confidence: 99%